Another Instance of ὀρθοποδεῖν - Winter, J. G. (Harvard theological review, 1941)
Readers of the Journal of Theological Studies may recall the interesting note by Mr. C. H. Roberts in the issue of January, 1939, vol. XL, no. 157, pp. 55–56. In connection with the occurrence of the verb in Galatians 2, 14 (ἀλλ᾽ ὅτε εἶδον ὅτι οὐκ ὀρθοποδοῦσιν πρὸς τὴν ἀλήθειαν τοῦ εὐαγγελίου κτλ.), Mr. Roberts calls attention to the appearance of the noun ὀρθοποδία in a recently published private letter of A.D. 117 (Papiri della R. Università di Milano, No. 24), which contains the sentence: νὴ τὴν σήν μοι σωτηρίαν καὶ τὴν τοῦ τεκνίου μου καὶ ὀρθοποδίαν, ἧς πέπεισμαί σε κήδεσθαι οὐκ ἔλασσόν μου κτλ.